OBSERVASI KEPUTUSAN BERKUNJUNG WISATAWAN PADA KAWASAN TAMAN WISATA ALAM GUNUNG TUNAK BERDASARKAN PENGARUH CITRA DESTINASI, PRODUK WISATA, DAN EWOM - Rionaldi Gigih Imam Pratama; Handry Sudiartha Athar; Lalu Muhammad Furkan (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
Taman Wisata Alam Gunung Tunak is located in Mertak Village, Pujut, Central Lombok, West Nusa Tenggara. Taman Wisata Alam Gunung Tunak has various potential tourist objects. This study aims to explain the influence of tourism products and electronic word of mouth on the decision to visit with destination images as a mediating variable in Gunung Tunak Nature Park. This research is a causal and associative research through a quantitative approach. The population in this study are visitors who visit the Taman Wisata Alam Gunung Tunak. The sample used in this study were 109 respondents with accidental sampling method. Based on the results of the analysis of the influence of tourism products and e-WOM on visiting decisions, it is concluded that the variables of tourism products and e-WOM have a significant positive effect on the variable of tourist decisions to visit in Taman Wisata Alam Gunung Tunak. Then the tourism product variables and e-WOM have a positive effect on the image of the destination, and the variable of destination image has a positive effect on the decision to visit. In addition, the variable of destination ctra also partially mediates the effect of wsata and e-WOM products on the decision to visit tourists.Keywords:Tourism Product, Electronic Word of Mouth, Destination Image, and Visit Decision